Evaluation of the effects of medium-term (57-day) omeprazole administration and of omeprazole discontinuation on serum gastrin and serum chromogranin A concentrations in the horse. - Clark B; Steel C; Vokes J; Shan JR; Gedye K; Lovett A; Sykes BW (John Wiley and Sons, Inc., 2023)
BACKGROUND: Rebound gastric hyperacidity (RGH) secondary to hypergastrinemia has been suggested to contribute to the rapid recurrence of equine squamous gastric disease (ESGD) in horses after discontinuation of omeprazole. HYPOTHESIS/OBJECTIVES: To evaluate changes in serum gastrin and chromogranin A (CgA) concentrations in response to medium-term (57-day) omeprazole treatment and after omeprazole discontinuation. ANIMALS: Fourteen mature Thoroughbred racehorses in simulated race training. METHODS: Horses received 2.28 g of oral omeprazole PO q24h for 57 days within a 61-day period, excluding a withholding period applied mid-protocol during which treatment was stopped as part of a concurrent study. Serum samples were collected on day 0 before omeprazole treatment, on day 1 of each week of the treatment period, and for an additional 5 weeks after discontinuation of treatment. Serum gastrin and CgA concentrations were analyzed using radioimmunoassay (RIA) and ELISA, respectively. RESULTS: Median serum gastrin concentrations increased 2.5-fold from baseline to day 7 (P < .001) but did not increase further during the omeprazole treatment period. Median serum gastrin concentrations returned to baseline within 2 to 4 days after administration of the last dose of omeprazole. No effect of treatment or discontinuation was seen in serum CgA concentrations. CONCLUSIONS AND CLINICAL IMPORTANCE: Serum gastrin concentrations increased in response to omeprazole treatment but returned to baseline within 2 to 4 days after the last dose of omeprazole. No effect of treatment or discontinuation was seen in serum CgA concentrations. Our results do not support the use of tapering protocols in horses.
Keywords: ESGD; equine; hypergastrinemia; rebound gastric hyperacidity; stomach; Horses; Animals; Omeprazole; Chromogranin A; Anti-Ulcer Agents; Gastrins; Stomach